PELATIHAN AKLIMATISASI ANGGREK Dendrobium BAGI REMAJA MUSALA DARUL IMAN KECAMATAN SUMBERSARI JEMBER - Restanto, Didik; Dewanti, Parawita; Handoyo, Tri; Soeparjono, Sigit; Hartatik, Sri; Slameto, Slameto; Siswoyo, Tri Agus; widjayanthi, Lenny; Avivi, Sholeh; Wulanjari, Distiana; Saleh, Azmi; Hazmi, Muhammad (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
The Dendrobium sp orchid is an orchid that is suitable for living in equatorial areas because it requires full light. Acclimatization is a very important stage for future orchid development. The aim of this service is to provide training to member of the Musala Darul Iman to understand orchid acclimatization techniques which can be used as equipment in orchid agribusiness. From the results of this trial, the audience's enthusiasm was obtained in listening to the lecture and practice, both in cultivation and agribusiness. Seedlings to be acclimatized should be healthy and perfect, good technique of transferring to a soft pot must be solid, watering was done after 7 days to give the root system the opportunity to develop well and required high levels of patience.